Hubungan Kunjungan Ibu ke Posyandu dengan Jumlah Balita Bawah Garis Merah (BGM) di Desa Tente Kecamatan Woha Kabupaten Bima - Nurlaila Fitriani (PALAPA, 2018)
Below the Red Line (BGM) toddler is a toddler whose weight is equal or below the red on a Card Towards the Healthy (KMS). Mothers who actively visit posyandu each month, then the developmental and nutritional status can be monitored by health workers through KMS that can reduce the incidence of cases of toddlers BGM. The purpose of this study was to determine the correlation between mother’s activeness in integrated health service with number reduction of toddler below the red line (BGM) in Tente village, Woha district, Bima regency. This research was a survey analytical, data was retrieved with crosssectional, the subjects of this study were two hundred and eighteen infants aged one to fifty-nine months. Data analyzed using chi-square test. Based on the research that has been done shows that mothers who actively visit posyandu but with BGM nutritional status of children was 34,5% while the mother is not active visit posyandu but the BGM nutritional status of children was 94,1% Based on the analysis of the research data using the chi-square test, showed that the p value = 0,000 with the significance level (alpha) of 0.05. Thus the p value is less than significant level (p less than alpha), so Ho is rejected which means that there is a correlation of mother's activeness with a reduction in the number of BGM toddler in the village Tente, Woha districk, Bima regency. Suggestions of this study are mothers are expected to be able to make the best use posyandu facilities monthly, because in addition to easy and cheap to get no-cost primary health care for their children, mother can also monitor the baby's growth and development regularly each month via KMS toddler book, so when there are problems about the baby's growth and development can be immediately addressed and assisted by health workers quickly and precisely.